Leptin and fractalkine: novel subcutaneous cytokines in burn injury - Dominic Friston; Sini Junttila; Julia Borges Paes Lemes; Helen Laycock; Jose Vicente Torres-Perez; Elizabeth Want; Attila Gyenesei; Istvan Nagy (The Company of Biologists, 2020)
Burn injury is a pathology underpinned by progressive and aberrant inflammation. It is a major clinical challenge to survival and quality of life. Although the complex local and disseminating pathological processes of a burn injury ultimately stem from local tissue damage, to date relatively few studies have attempted to characterise the local inflammatory mediator profile. Here, cytokine content and associated transcriptional changes were measured in rat skin for three hours immediately following induction of a scald-type (60°C, 2 min) burn injury model. Leptin (P=0.0002) and fractalkine (P=0.0478) concentrations were significantly elevated post-burn above pre-burn and control site values, coinciding with the development of burn site oedema and differential expression of leptin mRNA (P=0.0004). Further, gene sequencing enrichment analysis indicated cytokine-cytokine receptor interaction (P=1.45×10−6). Subsequent behavioural studies demonstrated that, following subcutaneous injection into the dorsum of the paw, both leptin and fractalkine induced mechanical allodynia, heat hyperalgesia and the recruitment of macrophages. This is the first report of leptin elevation specifically at the burn site, and the first report of fractalkine elevation in any tissue post-burn which, together with the functional findings, calls for exploration of the influence of these cytokines on pain, inflammation and burn wound progression. In addition, targeting these signalling molecules represents a therapeutic potential as early formative mediators of these pathological processes.